Unconventional monetary tools adopted by ECB and FED from 2008 until 2014 - Šetková, Lenka (2015)
Both the ECB and the Fed implemented various unconventional measures in response to the last crisis. While the ECB's policies were based on direct lending to banks, the FED adopted large-scale asset purchases. According to the empirical evidence these policies had economically beneficial effects in the US and the Eurozone but these measures have also certain spillovers which scope and exact impacts are quite difficult to estimate. There have been already many papers focusing on cross-border impacts of the FED's policies, but far less studied the spillovers of the ECB's policies. This work provides a theoretical background concerning the unconventional monetary policies implemented by the ECB and the FED after 2008 and analyse the impacts of ECB's policies on six particular countries outside euro area. The Impulse Responses of output, inflation, domestic interest rate and exchange rate are analyzed via block-restricted VAR model. My results confirm that euro area monetary policy does have an impact on non-euro area countries, although the response of macroeconomic variables in analysed countries are heterogeneous and also differ in the period before and after September 2008. Countries seem to be indeed affected more by conventional monetary policies until September 2008, but the euro-area monetary policy spills over via unconventional policies after September 2008. Overall, the ECB's policies affect economic activity outside euro area, but does not have significant impact on inflation. Furthermore, the exchange rate just initially drops in response to monetary tightening, but this reaction usually does not last for more than four months.